Trends and characteristics of ovarian conservation at hysterectomy for young women with cervical cancer. (June 2022) - Violette, Caroline J.; Mandelbaum, Rachel S.; Bainvoll, Liat; Joh, Sarah; Yessaian, Annie A.; Klar, Maximilian; Paulson, Richard J.; Roman, Lynda D.; Matsuo, Koji
Abstract: Objective: The association between early surgical menopause and increased mortality has been well demonstrated. Prior studies have also demonstrated that ovarian conservation is not associated with worse oncologic outcomes in early-stage cervical cancer. This study examined the contemporary trends and characteristics of ovarian conservation at time of hysterectomy in young women with cervical cancer. Methods: This is a retrospective cohort study examining the National Inpatient Sample. The study population was 4900 women aged ≤50 years with cervical cancer who had hysterectomy-based surgical treatment from 10/2015 to 12/2018. The exposure allocation was the adnexal procedure status (ovarian conservation versus oophorectomy). The main outcome measures were temporal trends of ovarian conservation over time and per patient age. Multivariable binary logistic regression model was fitted to identify independent characteristics associated with ovarian conservation. A classification-tree was constructed by recursive partitioning analysis to examine the utilization patterns of ovarian conservation. Results: A total of 2, 940 (60.0%) women underwent ovarian conservation at hysterectomy. Ovarian conservation rates remained stable until age 37 years, ranging from 82.5% to 77.9% ( P = 0.502), after which time the rate sharply and significantly decreased by 7.4% (95% confidence interval 5.4–9.3, P < 0.001) in one-year age increments from 77.9% at age 37 years to 28.7% at age 50 years. The rate of ovarian conservation increased from 54.7% in Q4/2015 to 64.4% in Q4/2018 ( P = 0.002). In multivariable analysis, recent surgery remained an independent factor for ovarian conservation (adjusted-odds ratio per year-quarter 1.04, 95% confidence interval 1.03–1.06). A classification-tree model identified 24 unique patterns of ovarian conservation based on patient factor (age, race/ethnicity, primary expected payer, and year of surgery), surgical factor (minimally invasive hysterectomy), and facility factor (hospital bed capacity and region), ranging from <20% to 90% (absolute percentage difference, >80%). Conclusion: Increasing rates of ovarian conservation at the time of hysterectomy in women undergoing surgical management of cervical cancer is encouraging; however, the marked decrease noted in patients in their mid-30s as well as substantial variability in ovarian conservation based on patient, surgical, and hospital factors are striking and warrant further consideration in clinical practice guidelines.